Conversations about beauty with ordinary Americans : "somebody loves us all" - Teres, Harvey M., 1950- (Common Ground Research Networks, 2018)
"This is a book that opens up an area of contemporary experience that rarely sees the light of day. I believe readers from all walks of life and different educational backgrounds will be as excited to read about these experiences as my subjects were delighted to talk about them. One measure of the public's interest in relevant oral history is the current popularity of Brandon Stanton's Humans of New York, Stories, found in museums and bookstores throughout the city. And the fact that the recent Nobel went to Svetlana Alexievich, a writer whose work is grounded in oral history, will expand the market for such books, and is a sign that more and more readers are interested in what ordinary people, whose voices are usually muted, have to say about crucial aspects of modern life. The book's interdisciplinary appeal will attract faculty and students in cultural studies, English, sociology, and other departments and programs interested in aesthetics. The book will have considerable crossover appeal to a wide general audience that especially includes women (most of my subjects are women) and women of color (a third of my subjects are members of a minority). The book is, in fact, eminently "Oprah-ble" because of its undoubted appeal to her vast audience. The challenge for an academic press, of course, will be to gain this audience's attention, a task to which I will be more than happy to devote substantial time and effort"--